Phylogenetic and genomic analyses of two new species of Clavispora (Metschnikowiaceae, Saccharomycetales) from Central China - Chai, Chun-Yue; Li, Ying; Yan, Zhen-Li; Hui, Feng-Li (Frontiers in Microbiology, 2022)
Species in the genus Clavispora have previously been reported primarily in the northeast and northwest regions of China; the species diversity of Clavispora in central China is not currently clear. In this study, phylogenetic inferences of Clavispora based on sequences of a single-locus (LSU D1/D2) and a two-locus (LSU D1/D2 and ITS) were conducted. Two new species isolated from rotting wood in central China, namely Clavispora xylosa sp. nov. and Clavispora paralusitaniae sp. nov., were delimited and proposed based on morphological and molecular evidence. Cl. xylosa was closely related to C. thailandica CBS 10610T, but with 11.5% divergence in the LSU D1/D2 domains and 11.5% divergence in the ITS regions. Cl. paralusitaniae was a sister to Cl. lusitaniae CBS 6936T from which it differs with 4.65% divergence in the LSU D1/D2 domains and 5.39% divergence in the ITS regions. Description of Cl. xylosa sp. nov. and Cl. paralusitaniae sp. nov. was also supported by morphological comparisons and genomic analyses between the two new species and their closest relatives, C. thailandica CBS 10610T and Cl. lusitaniae CBS 6936T. These results indicate a potentially great diversity of Clavispora spp. inhabiting rotting wood in central China, ripe for future discovery.